MEKTEPKE ShEKEMGI HÁM KIShI MEKTEP JASÍNDAǴÍ TUTLÍǴÍP SÓYLEYTUǴÍN BALALARDÍ LOGOPEDIYALÍQ TEKSERIWDIŃ ÁHMIYETI - Tajimuratova, K. (SCIENCE and SOCIETY, 2025)
This article highlights the importance of identifying children's tendency to stutter from an early age, the methods of correcting stuttering observed in children with speech therapy correction work, and their implementation.